Sicilian amphorae (1st–6th centuries ad): typology, production and trade - Franco, C (2014)
This thesis is a comprehensive investigation of the transport containers produced in Roman Sicily over a chronological period composed of five phases: Early Roman period (30 BC–AD 100); Middle Roman period (AD 100–300); Late Roman period (AD 300–440); Vandal Perios (AD 440/535) and Early Byzantine period (AD 536/600). The research investigates the production and transportation of Sicilian foodstuffs (especially wine) from the major ports of the island to Mediterranean ports and northern Europe. The results demonstrate the wide distribution of Sicilian amphorae and their important role within the wider economy of the Roman Empire. The importance of this research lies in the fact that, despite the agricultural prosperity of Sicily in the Roman Period and its strategic topographical position, transport amphorae remain understudied especially in economic terms. In regards to typology, chronology and distribution, our current knowledge of regional containers has not reached a level comparable to that of amphorae manufactured in other territories. The key discussion focuses on the commercial dynamics of Roman Sicilian amphorae from local, regional and Mediterranean-wide perspectives. The research aims to outline the distribution trends of Sicilian amphorae, looking at the different relative quantities of each amphora type and consequently the extent to which they are present in regions inside and outside Sicily, while considering presences and absences within the more general and homogeneous context of the Mediterranean basin. The organisation of Sicilian amphora production is also tackled through the presentation of probable production sites and excavated kilns. Using these examples, the study investigates the management of production of these containers on the island. The initial data obtained by this research represents a first step in determining differences between Sicilian amphorae workshops producing amphorae — therefore trading wine — for Mediterranean export and manufacturing sites specializing in local/regional trade. Other key achievements include the creation of a new illustrated typology with profile drawings of all the amphora forms and a summary and catalogue of Sicilian amphorae fabrics. In the thesis, the results of archaeometric analysis (thin-sections) carried out on more than 120 Sicilian amphora samples, provided by numerous institutions in Sicily and abroad, are presented. These results add significantly to our knowledge of the fabric composition, manufacture technology, origin and consequently movement of these amphorae around the Mediterranean over six centuries. More generally the research shows that the study of Sicilian material culture along with archaeological evidence is essential for recording the economic dynamics of Sicily, with the intent of dispelling the stereotype that Sicily's primary role was as a grain supplier to Rome. Besides grain — widely produced and exported throughout the imperial period, as attested by ancient sources and inscriptions — the archaeological evidence clearly indicates the export of foodstuffs, especially wine, at an inter-provincial level from the 1st until the second half of the 6th century AD.